ANALISIS STRUKTUR GERAK TIDI LO TONGGALO DI KECAMATAN TAPA PROVINSI GORONTALO - Nur Aprilia Ismail; Riana Diah Sitharesmi; Rahmawati Ohi; Trubus Semiaji; Nurlia Djafar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Tidi Lo Tonggalo is one of several types of Tidi, where Tidi means “dance” and Tonggalo means “support”. Thus, Tidi Lo Tonggalo symbolizes how a woman acts as a pillar in the family, society, and religion, emphasizing that if she falters, so too will what she supports. Tidi Lo Tonggalo possesses a beautiful movement structure, rich with values and meanings. Analyzing its movement structure helps facilitate an accurate and clear interpretation of the dance. This qualitative descriptive study employs data collection through observation, interview, and documentation. The qualitative data analysis was continuous and iterative, involving data reduction, data display, and conclusion drawing or verification, representing the research’s success indicators. The study was conducted in Tapa Sub-district, Gorontalo Province. This dance is performed by five women and serves an entertainment function. The analysis findings of Tidi Lo Tonggalo’s movement structure are based on its compositional elements: vocabulary, spatial design, and dynamics. There are 32 movement vocabularies or poses in Tidi Lo Tonggalo, with transitional movements and repetitions on the right and left sides of the body in each sequence. The dance features nine spatial designs or floor patterns, some similar but incorporating different movements. Additionally, its dynamics are marked by changes in tempo in the musical accompaniment. Despite the tempo changes, the dancers maintain the softness of their movements throughout the performance.